Adverse selection, commitment and exhaustible resource taxation - Julie Ing (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Governments design taxation schemes to capture resource rent. However, they usually propose contracts with limited duration and possess less information on the resources than the extractive firms do. This paper investigates how information asymmetry on costs and an inability to commit to long-term contracts affect tax revenue and the extraction path. This paper assumes that governments maximize the tax revenue contingent on the quantity extracted. This study gives several unconventional results. First, when information asymmetry exists, the inability to commit does not necessarily lower tax revenues. Second, under asymmetric information without commitment, an efficient firm may produce during the first period more or less than under symmetric information. Hence, the inability to commit has an ambiguous effect on optimal contract duration. Third, an increase in the discount factor may shift the extraction towards the first period which contradicts Hotelling's rule.
Keywords: Q38; D86; H21; 330; resource taxation; asymmetric information; commitment; Erschöpfbare Ressourcen; Optimale Besteuerung; Asymmetrische Information; Adverse Selektion; Steuereinnahmen; Hotelling-Regel; Theorie